Preference for different intensities of red light as affected by the age, temporal variation and behaviour of broiler birds - D. Senaratna; T. S. Samarakone; W. W. D. A. Gunawardane (Tropical Agricultural Research, 2015)
The red light (RD) marks high preference (PR), weight gain and welfare of broilers. A study was conducted to determine the PR for high (HI; 320 lux), medium (MI; 20 lux), dim (DI; 5 lux) intensities of RD and to investigate whether such PRs are influenced by age (AG), temporal variation (TV) and behaviour. The PR-chambers consisting of three identical compartments were provided with ad libitum feed, water and illumination from 5W incandescent bulbs (20 lux, 20 L:4D). A randomized complete block design was used with six replicates. Five birds were initially confined to the centre of each experimental unit (24 hrs.) and then allowed to move freely. Their presence under respective light intensity (LI) was recorded with behaviour adopting scan sampling. Data were analyzed using ANOVA procedure (a=0.05). The PR was significantly affected by AG, TV and behaviour, i.e. walking [Wk] and lying [Ly]. At the week 2 (wk 2) the highest (87%) and the lowest (3%) PRs were marked for HI and DI, respectively, in the night (NT). Young birds (14 d) preferred HI to DI, and the opposite was recorded with AG advancement. Irrespective of the AG, the highest PR was recorded for DI in the morning (MN) and HI in the NT. The reason could be that low intensities are associated with the cooling effect. The LI*TV*AG significantly affected on Ly and Wk. The highest Wk (87.29 % ± 0.05) was observed in the NT under HI at wk 2 and the highest Ly (39.95 % ± 0.08) was performed in the evening in DI at wk4. At the wk 2, all activities occurred mostly in HI; whereas at wk 5, Ly and sleeping (Sl) were dominant in DI. It is concluded that PR for different intensities of RD varies with AG advancement, temporal variation of the day, and certain behaviours (mainly Wk and Ly) of broiler birds. Older birds were inactive and preferred to perform Ly and Sl under DI.   Tropical Agricultural Research Vol. 25 (2): 146 – 157 (2014)